STUDY OF TRAFFIC JUNCTION WITH A TIME - AND TRANSPORT -DEPENDENT CONTROL (Municipal economy of cities (Technical science), 2013)
We consider time- dependent and transport- dependent traffic control at intersections controlled , analyzes their advantages and disadvantages. Shows a graph of intensity of arrival of vehicles to cross . <span title="З використанням імітаційного моделювання проведено дослідження функціонування перехрестя з різними системами керування та встановлено, що застосування транспортно-залежного керування з нечітким алгоритмом керування є більш ефективним, ніж часово-залежного.">Using simulation studies carried out with different cross functioning control systems and found that the use of transport- dependent control with fuzzy control algorithm is more efficient than time- dependent .